Application of Ethical Principles to Research using Public Health Data in The Global South: Perspectives from Africa. Issue 2 (22nd December 2016) - Anane‐Sarpong, Evelyn; Wangmo, Tenzin; Sankoh, Osman; Tanner, Marcel; Elger, Bernice Simone
Abstract: Existing ethics guidelines, influential literature and policies on ethical research generally focus on real‐time data collection from humans. They enforce individual rights and liberties, thereby lowering need for aggregate protections. Although dependable, emerging public health research paradigms like research using public health data (RUPD) raise new challenges to their application. Unlike traditional research, RUPD is population‐based, aligned to public health activities, and often reliant on pre‐collected longitudinal data. These characteristics, when considered in relation to the generally lower protective ethico‐legal frameworks of the Global South, including Africa, highlight ethical gaps. Health and demographic surveillance systems are examples of public health programs that accommodate RUPD in these contexts. We set out to explore the perspectives of professionals with a working knowledge of these systems to determine practical ways of appropriating the foundational principles of health research to advance the ever growing opportunities in RUPD. We present their perspectives and in relation to the literature and our ethical analysis, make context relevant recommendations. We further argue for the development of a framework founded on the discussions and recommendations as a minimum base for achieving optimal ethics for optimal RUPD in the Global South.